Oil droplet cataracts can mimic retinal disease - Abraham Ifrah, MS; Janet S. Sunness, MD (American Journal of Ophthalmology Case Reports, 2022)
Purpose: Oil Droplet Cataracts in adults is an elusive diagnosis for ophthalmologist. It is difficult to diagnose, and patients can suffer for years with increasingly debilitating symptoms for what is a surgically curable condition. Additionally, patients often undergo difficult and costly medical testing as well as occasionally receive improper treatment. This case series goal is to highlight this condition, showing that with careful slit lamp examination and index of suspicion one is able to appropriately diagnose this condition and avoid unnecessary testing and harm to a patient's quality of life. Methods: Nine cases of this diagnostically challenging condition seen by one of the authors of this paper (JSS) are included. All were referred for electrophysiological or careful testing for unexplained visual loss, by neuroophthalmologists and/or retina specialists. Three were suspected of having a retinal dystrophy. Many had already undergone MRI and extensive evaluations. Results: All patients were women. The average age was 45.5 years old with a range of 32–52 years of age on at their initial visit. The average length of symptoms prior to the initial visit was 3.2 years with a range of 3 months–11 years and a median of 4 years. Six had uniocular oil droplet cataracts, and three had binocular involvement. At diagnosis of the affected eyes, visual acuity ranged from 20/30–1 to 20/160 with a median of 20/65 in the affected eyes. Five patients had monocular diplopia or triplopia. Four had myopic shifts. Six patients had cataract surgery with resolution of their symptoms and restoration of good visual acuity. One patient who had been prescribed a low vision telescope for her presumed retinal dystrophy recovered to 20/20- ou, and had normalization of her electroretinogram after cataract surgery. Conclusions: This case series shows the diagnostic difficulty of this condition and the years it could take before a definitive diagnosis is made. Slit lamp examination was able to successfully diagnose this condition, although sometimes the oil droplet cataract was not seen until a later visit. Oil droplet cataracts should be considered in the differential diagnosis for a patient presenting with unexplained visual loss or acute worsening visual difficulties, and may mimic a retinal dystrophy. Once diagnosed, cataract surgery can cure this condition.(Abraham Ifrah, Janet S Sunness; Oil Drop Cataracts Mimicking Retinal Disease. Invest. Ophthalmol. Vis. Sci. 2020;61(7):3851).